Raising Darwin's Consciousness: Females and Evolutionary Theory - Hrdy, Sarah Blafler (Zygon, 1990)
Early studies of primate social behavior were distorted by observational, methodological, and ideological biases that caused researchers to overlook active roles played by females in the social lives of monkeys. Primatology provides a particularly well documented case illustrating why research programs in the social and natural sciences need multiple studies that enlist researchers from diverse backgrounds